Two-dimensional computational modeling of the electrokinetic remediation of a copper-contaminated soil part i: model validation (2014)
A two-dimensional computational model for the electrokinetic remediation of copper from a contaminated soil is presented. The model is an adaptation of the original code developed by one of the authors, in which the chemical composition and transport of the copper species in solution were incorporated. The model includes electromigration, electroosmosis, ordinary diffusion, and convection transport mechanisms, it assumes local chemical equilibrium and unsteady state conditions. An artificially contaminated soil from Cananea, Mexico was used as an example. The model predictions were compared with experimental data collected in a laboratory, circular-shaped soil in which a central anode and four cathodes in the periphery were inserted. A reasonable agreement between the predicted and the experimental values was obtained in terms of the spatial distributions of pH and copper concentration. The potential applications of the computational model are discussed.